Neurologic Outcomes of Complex Adult Spinal Deformity Surgery: Results of the Prospective, Multicenter Scoli-RISK-1 Study. Issue 3 (February 2016) - Lenke, Lawrence G.; Fehlings, Michael G.; Shaffrey, Christopher I.; Cheung, Kenneth M.C.; Carreon, Leah; Dekutoski, Mark B.; Schwab, Frank J.; Boachie-Adjei, Oheneba; Kebaish, Khaled M.; Ames, Christopher P.; Qiu, Yong; Matsuyama, Yukihiro; et al.
Abstract : Study Design: Prospective, multicenter, international observational study. Objective: To evaluate motor neurologic outcomes in patients undergoing surgery for complex adult spinal deformity (ASD). Summary of Background Data: The neurologic outcomes after surgical correction for ASD have been reported with significant variability and have not been measured as a primary endpoint in any prospective, multicenter, observational study. Methods: The primary outcome measure was the change in American Spinal Injury Association (ASIA) Lower Extremity Motor Scores (LEMS) obtained preoperatively, and at hospital discharge, 6 weeks and 6 months postoperatively. Results: A total of 273 patients with complex ASD underwent surgery at 15 sites worldwide. One patient was excluded for lack of preoperative LEMS. The remaining 272 patients were divided into two groups: normal preoperative LEMS (=50) (Preop NML, N = 204, 75%) and abnormal preoperative LEMS (<50) (Preop ABNML, N = 68, 25%). At hospital discharge, 22.18% of patients showed a decline in LEMS compared with 12.78% who showed an improvement. At 6 weeks, there was a significant change compared with discharge: 17.91% patients showed a decline in LEMS and 16.42% showed an improvement. At 6 months, 10.82% patients showed a decline in preoperative LEMS, 20.52% improvement, and 68.66% maintenance. This was a significant change compared with 6 weeks and at discharge. Conclusion: Although complex ASD surgery can restore neurologic function in patients with a preoperative neurologic deficit, a significant portion of patients with ASD experienced postoperative decline in LEMS. Measures that can anticipate and reduce the risk of postoperative neurologic complications are warranted. Level of Evidence: 3